BIMBINGAN PEMBELAJARAN PAI UNTUK ANAK TUNALARAS - Annisa Aulia; Muhammad Riesqi; Raudina Rahma Artyadi; Arifani Maulida Rahman (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
Every human being is created by God with all forms of merit, for man is the most perfect creation in this universe. Man is equipped with reason and mind intended to be used and developed in order to give good to other human beings. The data collection techniques used in making this scientific paper use literature study techniques or collecting relevant journal sources. Education can be taken by anyone, including children with special needs (ABK). Education is not for competition but to change people for the better and smarter. Children with special needs are also required to get an education like other children. The disabled are one of the children with special needs who have social and emotional behavior disorder disorders. With deep care about the character of the child and giving more attention to the child, especially Islamic education. By providing guidance on Islamic religious education lessons, it is hoped that it will be able to provide spiritual insight and can create a generation that has a noble character and can return to the true human nature.